Case Study Of "Burger 0 Myy" / Siti Sarah Zalikha Umar Baki ... [et. al] - Umar Baki, Siti Sarah Zalikha; Norhissham, Nur Hafiza; May, Masnoni; Andam, Jespeny Kiki; Aben, Sheereen Puyang (2019)
The case study is important to evaluate the company’s background, organizational chart, operational and marketing strategy, profit and budget, product, future plan, company’s analysis as well as the company’s problems, and alternatives that the management has provided. The way to use to study analysis is by face-to-face interviews or through phone calling to get more information from the company. In addition, we also can conduct a questionnaire from people who already purchased and tasted the product. Based on the company that we has been interviews is Burger ’O’ Myy. This business started on 4, 2017 Mr Razif bin Muhd Yunus, the owner of the company and has 3 branches which are at Taman Samarindah Kota Samarahan, Desa Ilmu Kota Samarahan and Metrocity Matang. Burger ’O’ Myy was very famous among students UiTM Kota Samarahan and for those who love to eat western foods.